Development of Visual Target Media as a Passing Training Aid for Football Schools - Daru Dwi Kurnianto; Martin Sudarmono (Gladi : Jurnal Ilmu Keolahragaan, 2026)
Limited training facilities cause players to become bored, especially in soccer passing training materials. The purpose of this study is to produce a visual target media product as a passing training aid for soccer schools. This research is a development research using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The data collection instrument used is a questionnaire. The data analysis used is quantitative descriptive analysis and qualitative descriptive analysis. A small-scale trial was conducted on 14 players of the Garuda Muda SSB club. While a large-scale trial was conducted on 40 players from 2 SSB clubs, namely Garuda Muda and Putra Mandiri. The instruments in this study used observation, interview, and questionnaire techniques. Validation of this study used material experts and media experts. The data analysis technique in this study used a Likert scale for expert validation and a Guttman scale for questionnaires on players. The results of the study are as follows: (1) The validation data according to experts is 72% with a sufficient category. (2) The results of the small-scale trial were 83% in the Good category, and (3) the results of the large-scale trial were 87% in the Good category. The product resulting from this development is a visual raft target goal (GATRAVIS) that can be assembled and disassembled. The visual raft target goal media (GATRAVIS) has been declared suitable for use as a passing training aid, the media remains effective when applied to broader training situations in soccer schools.